Synthetic fiber on roads at the state of affirmation and its effect on its mechanical properties, Puno Region - Mamani Mamani, Fausto Ponciano (2019)
The present investigation arises through the observation of the different structural problems that appear in the affirmed ones. These deteriorations are diverse and many of them are the product of the poor quality of the materials used in the construction of the affirmed roads. Objective is to determine the impact of the mechanical properties of the roads at the level of the reinforced synthetic fibers in the province of Moho, in the year 2017. The comparison of the mechanical properties of the synthetic without adding synthetic fiber was carried out. with respect to deformation (mm) (1), versus the mechanical properties of affirmed with the addition of synthetic fibers with 0.1% of the weight of soil in terms of deformation (mm) (2). For this, Pearson's r correlation was applied and it was determined how it affects the design of the affirmed. The Pearson r correlation was used. The level was experimental, applicative and correlational. It requires 0.1% of polypropylene fiber per weight of the loose one in order to improve the resistance to the cutting effort of a truck of 3.44 tons in a wheel; in the same way, produce an increase of the CBR to reduce the thickness of the initial one in 2cm.